2017
DOI: 10.1140/epjh/e2017-80014-4
|View full text |Cite
|
Sign up to set email alerts
|

Stellar structure and compact objects before 1940: Towards relativistic astrophysics

Abstract: Since the mid-1920s, different strands of research used stars as "physics laboratories" for investigating the nature of matter under extreme densities and pressures, impossible to realize on Earth. To trace this process this paper is following the evolution of the concept of a dense core in stars, which was important both for an understanding of stellar evolution and as a testing ground for the fast-evolving field of nuclear physics. In spite of the divide between physicists and astrophysicists, some key actor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 218 publications
0
16
0
Order By: Relevance
“…First, the density required to create such an object was far from any that had yet been observed. The estimate of the density of white dwarfs was already controversial and was a point of criticism of Eddington's model in the first half of the 1920s [Bonolis 2017]. Another point of discontent was the appearance of singularities in the Schwarzschild solution.…”
Section: The Equilibrium Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…First, the density required to create such an object was far from any that had yet been observed. The estimate of the density of white dwarfs was already controversial and was a point of criticism of Eddington's model in the first half of the 1920s [Bonolis 2017]. Another point of discontent was the appearance of singularities in the Schwarzschild solution.…”
Section: The Equilibrium Hypothesismentioning
confidence: 99%
“…The history of astrophysical and astronomical researches on dense objects from the beginning of the 20th century up to the 1940s was outlined by Luisa Bonolis in [Bonolis 2017], while Jean Eisenstaedt recounted how the Schwarzschild solution was perceived during the first years after the birth of general relativity in works such as [Eisenstaedt 1982] and [Eisenstaedt 1993]. Werner Israel delineated the evolution of the concept of dark stars into black holes in [Israel 1987], offering a narrative of the history up to the mid-1980s.…”
Section: Introductionmentioning
confidence: 99%
“…For simplicity, let us assume that the specific intensity is isotropic (independent of α ) and that the hot spot is small in size. Writing I 0 (α ) = I 0 , normalizing the flux dF by I 0 dA /D 2 we have 4 .…”
Section: E the Bolometric Flux In Scalar-tensor Gravitymentioning
confidence: 99%
“…The Schwarzschild radius defines the boundary of the Schwarzschild black hole. There was new interest in the 1930s' work of Robert Oppenheimer, and his students George Volkoff and Hartland Snyder, on neutron stars and the spherically symmetric collapse of a body, such as a star, to form a black hole (Oppenheimer and Volkoff 1939;Oppenheimer and Snyder 1939;Bonolis 2017). They had shown that for a sufficiently large mass there is no final stable equilibrium state as a white dwarf or as a neutron star.…”
Section: Years Of Change 51 Backgroundmentioning
confidence: 99%